Invited review: dysregulation of chromatin remodellers in paediatric brain tumours - SMARCB1 and beyond - Johann, Pascal-David (Neuropathology & applied neurobiology, 2020)
Mutations in chromatin remodelling genes occur in approximately 25% of all human tumours (Kadoch et al. Nat Genet 45: 592-601, 2013). The spectrum of alterations is broad and comprises single nucleotide variants, insertion/deletions and more complex structural variations. The single most often affected remodelling complex is the SWI/SNF complex (SWItch/sucrose non-fermentable). In the field of paediatric neuro-oncology, the spectrum of affected genes implicated in epigenetic remodelling is narrower with SMARCB1 and SMARCA4 being the most frequent. The low mutation frequencies in many of the SWI/SNF mutant entities underline the fact that perturbed chromatin remodelling is the most salient factor in tumourigenesis and could thus be a potential therapeutic opportunity. Here, I review the genetic basis of aberrant chromatin remodelling in paediatric brain tumours and discuss their impact on the epigenome in the respective entities, mainly medulloblastomas and rhabdoid tumours.
Gesehen am 07.01.2021